A Competencies Approach to Assessment of University Teaching Staff - E V Maslov (RUDN Journal of Psychology and Pedagogics, 2011)
The article considers the key requirements to the teacher of the modern higher school on the basis of competencies approach. The advantages of this approach for the evaluation and development of university teaching staff are discussed. The original model of competencies for teachers of the University is proposed.